Experimental research on the law of the deformation and damage characteristics of raw coal/ briquette adsorption-instantaneous pressure relief. (15th January 2022) - Zhou, Aitao; Du, Chang'ang; Wang, Kai; Hu, Jiaying; Fan, Xihui
Highlights: The deformation characteristics of briquette/raw coal was discussed. The adsorption characteristics of coal to different gases were studied. Analysis of macroscopic damage and failure characteristics of coal. Abstract: In order to clarify the characteristics of gas-bearing coal adsorption-instantaneous pressure relief deformation, and reveal the mechanism of the effect of gas desorption on the outburst. Through the gas-bearing coal adsorption-instantaneous pressure relief test system, the adsorption-instantaneous pressure relief test using briquette/raw coal samples was used to conduct a comprehensive comparison and analysis of the deformation characteristics of the two coal samples. Studying the damage of coal with different adsorption characteristics gases under the condition of adsorption-instantaneous pressure relief, and use strain gauges to monitor the microscopic deformation of the coal, and analysis of the adsorption of briquette/raw coal at constant pressure-instantaneous similarities and differences of deformation characteristics during pressure relief. "The results showed that under the same test conditions of adsorption equilibrium pressure, the degree of crushing of coal samples after instantaneous pressure relief is CO2  > CH4  > N2 . At the moment of instantaneous pressure relief, the strain of the raw coal/briquette suddenly decreases, characterized by swelling deformation. Under the same temperature and pressure conditions, the expansion energy of CO2 is the highest, followed by CH4 and N2 . Due to the raw coal has not completely destroyed the joints, only elastic deformation occurs, and the strain rises rapidly within a short period of time, resulting in shrinkage deformation. However, during the instantaneous pressure relief of the briquette, swelling and deformation occurred, and the coal was destroyed. The research results have certain significance for the exploration of coal and gas outburst mechanism.